Fatal neurotoxic envenomation following the bite of a greater black krait (Bungarus niger) in Nepal: a case report - Deb Prasad Pandey; Sanjib Kumar Sharma; Emilie Alirol; François Chappuis; Ulrich Kuch (Journal of Venomous Animals and Toxins including Tropical Diseases, 2016)
Abstract Background Neurotoxic envenomation following bites by kraits (Bungarus species) is a leading cause of snakebite mortality in South Asia. Over a long time, this had been attributed only to one species, the common krait (Bungarus caeruleus). However, recent research has provided increasing evidence of the involvement of several krait species. Here, we report a fatal case of neurotoxic envenomation following the bite of a greater black krait (Bungarus niger) in Nepal. Case presentation A 33-year-old man was bitten in the outdoor corridor of his home in the eastern hills of Ilam district while handling a snake he thought to be non-venomous. He subsequently developed severe abdominal pain, frequent vomiting, and signs of neurotoxic envenomation leading to respiratory paralysis. The patient did not respond to Indian polyvalent antivenom given 4 h after the bite and died under treatment 8 h after the bite. This is the second time that a B. niger was observed in Nepal, the first documented case of envenomation by this species in the country and the sixth reported case worldwide. Conclusions Previous distribution records – from eastern India and western Nepal, from western hills in Nepal, and from lowland localities in India and Bangladesh – indicate risk of envenomation by B. niger throughout the low and intermediate elevations of Nepal up to at least 1,500 m above sea level. As very few people in Nepal bring killed snakes to healthcare centers and because there is a general belief among local people that there are no kraits in the hills, bites by B. niger are likely to be misdiagnosed and underreported.